A descriptive cross-sectional study of helicobacter pylori infection in non-ulcer dyspepsia patients in a tertiary care teaching hospital In the Eastern part of Nepal (Journal of Nobel Medical College, 2016)
Background In Gastroenterology practice, worldwide, the most common cause of dyspepsia is functional. Functional or non-ulcer dyspepsia is established by gastroduodenoscopy which rules out structural disorders in dyspeptic patients. Helicobacter pylori, a gram-negative bacterium in gastric mucosa is associated with non-ulcer dyspepsia, chronic gastritis, gastriculcer and cancer. Worldwide prevalence of Helicobacter pylori infection is higher but its association with non-ulcer dyspepsia is less clear.Material and Methods The aim of this study was to see the prevalence of H. pylori infection in non-ulcer dyspepsia. A cross-sectional study of 340 patients presented at Nobel Teaching Hospital in one year with dyspeptic symptoms underwent clerking, physical examination, gastroduodenoscopy and RUT. Symptomatic patients without any structural lesions were designated as functional dyspepsia. RUT when turned red indicated positive for H. pylori infection.Result Out of 340 patients, 180 (52.9%) were female and 160(47.1%) were male. Mean age of male and female patients was 35.88 ± 11.8 and 38.11 ± 11.7 respectively. Amongst all participants 150 (44.11%) were housewives and 69(20.3%) were students. Endoscopic findings showed gastritis 205(60.29%) and duodenitis 15(4.42%). RUT was found positive in 62% of gastritis and 86.7% of duodenitis patients (p value=0.001).Conclusion High prevalence of H pylori infection in present study may be one of the causative factors in producing symptomatic non-ulcer dyspepsia. Hence, early detection and complete eradication of H.pylori infection is mandatory. It will reduce usage of PPIs and also improve quality of life.Journal of Nobel Medical College Vol.5(2) 2016; 10-16